Changes in the West African forest-savanna mosaic, insights from central Togo. - Honam Komina Atsri; Yawo Konko; Aida Cuni-Sanchez; Komla Elikplim Abotsi; Kouami Kokou (PLoS ONE, 2018)
The West African forest-savanna mosaic, an important habitat for biodiversity and humans, is severely degraded, fragmented and modified by human activities. However, few studies have quantified the land cover changes observed over time and/or analysed the drivers of change. This study focused on Fazao-Malfakassa National Park, the largest in Togo, uses a combination of remote sensing, ground surveys and questionnaires to: (i) quantify vegetation changes, (ii) determine the drivers of change, (iii) compare results with findings elsewhere in the region and (iv) suggest management interventions. The images used were Landsat 5 TM, Landsat 7 ETM and Sentinel-2. Different vegetation indices were computed including: number of fragments, index of dominance, mean area of a vegetation type and mean annual expansion rate. In total, 300 people (including park staff and local populations) were interviewed using a semi-structured questionnaire. Results indicate that between 1987 and 2015 closed-canopy forest and tree-savanna became severely degraded and fragmented, following trends in other parts of the West African forest-savanna mosaic. The main drivers of change were agricultural expansion, bush fires and timber extraction. Observed changes and drivers altered with time: e.g. agricultural expansion was greatest during 1987-2001 (linked with political instability) while illegal timber extraction augmented during 2001-2015 (following increased timber value). Park staff and local populations' perceptions on drivers of change did not differ. Our study highlights that action is urgently needed if we are to preserve this important habitat, the biodiversity it hosts and the services it provides to humans. We suggest several management interventions, learning from successful interventions elsewhere in the region.